Nanoarquitetura em sistemas de alumina anódica porosa e configurações magnéticas de partículas de Co eletrodepositadas - Cardoso, Márcia Lourenço (2005)
This thesis presents results on tailoring porous anodic alumina films, the Co-CoO electrodeposition on alumina template and the magnetic behavior of such system. Mono and bi-modal pore distribution at the film surface were obtained in a two-step anodization. It was observed the growth of non parallel pores when temperature or current were modified from the first to the second step. The current plays the great role in the top layer morphology modification. The Co ions were electrodeposited on regular Al2O3 membrane under an sine waveform potential. This procedure provided the formation of a granular system of Co-CoO. For small times of deposition the sample presents major value of the coercive field in the perpendicular to plan of the substrate direction. Carrying out the electrodeposition for a long period the magnetization easy axis goes to the sample surface plane, where the coercive field was major. The existence of Co oxide was inferred through of magnetization measurements. It was detected "exchange bias" fields, results of the coupling between antiferromagnetic/ferromagnetic portion of the sample. This phenomenon was observed in both directions of the samples at 250 K. The results also show the domain formation on a antiferromagnetic portion at the ferro/antiferromagnetic interface. Such domains were allowed to rotation near the blocking temperature.